2015
DOI: 10.1161/circimaging.114.003036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Impact of a New Left Ventricular Ejection Index in Primary Mitral Regurgitation Because of Mitral Valve Prolapse

Abstract: Background— To prevent left ventricular dysfunction (LVD), surgery is recommended in patients with severe primary mitral regurgitation as soon as ejection fraction (EF) ≤60% or LV end-systolic diameter ≥40 mm. However, LVD may be concealed behind preoperative normal LVEF and LV end-systolic diameter. We sought to identify whether a new composite echocardiographic Doppler marker of the LV ejection according to the LV dilatation may predict postoperative LVD and outcome after mitral valve repair in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Hence, these findings suggest that, although it does not reflect the true LVEF, the forward LVEF is more sensitive than the total LVEF to detect subclinical LV dysfunction and predict risk of adverse events in primary MR. Consistent with our results, Magne et al recently reported that the “LV ejection index,” calculated by dividing the indexed LV end‐systolic diameter by LV outflow tract time‐velocity integral, was a better predictor of mortality and LV dysfunction after surgery than total LVEF . Our results, however, suggest that forward LVEF may be superior to the LV ejection index to predict outcomes in primary MR, especially the need of MV surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, these findings suggest that, although it does not reflect the true LVEF, the forward LVEF is more sensitive than the total LVEF to detect subclinical LV dysfunction and predict risk of adverse events in primary MR. Consistent with our results, Magne et al recently reported that the “LV ejection index,” calculated by dividing the indexed LV end‐systolic diameter by LV outflow tract time‐velocity integral, was a better predictor of mortality and LV dysfunction after surgery than total LVEF . Our results, however, suggest that forward LVEF may be superior to the LV ejection index to predict outcomes in primary MR, especially the need of MV surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, Magne et al recently reported that the "LV ejection index," calculated by dividing the indexed LV end-systolic diameter by LV outflow tract timevelocity integral, was a better predictor of mortality and LV dysfunction after surgery than total LVEF. 21 Our results, however, suggest that forward LVEF may be superior to the LV ejection index to predict outcomes in primary MR, especially the need of MV surgery. Several studies 15,29,35 reported that a substantial proportion of patients may have a significant deterioration of total LVEF immediately after MV surgery.…”
Section: Discussionmentioning
confidence: 56%
“…We should discuss why moderate or severe MR was significantly associated with prolonged hospitalization. Because patients in the present study were very elderly (83.7 ±5.1 years old), the etiology of MR would be secondary such as volume over caused by heart failure rather than primary such as mitral valve prolapse [23,24]. As peri-operative ADHF was the second most common reason for prolonged hospitalization, moderate or severe MR might reflect the severity of ADHF before trans-femoral TAVI.…”
Section: Discussionmentioning
confidence: 90%
“…A LV ejection index >1.13 is associated with post-operative LV dysfunction and mortality, even in patients with a pre-operative LVEF >60%. 14 Although not included in the guidelines as part of the surgical criteria, it is nevertheless a handy parameter that takes into account both the size and function of the LV.…”
Section: 11mentioning
confidence: 99%